Elastin in the Liver - Kanta, Jiří (Frontiers in Physiology, 2016)
A characteristic feature of liver cirrhosis is the accumulation of large amounts of connective tissue with the prevailing content of type I collagen. Elastin is a minor connective tissue component in normal liver but it is actively synthesized by hepatic stellate cells and portal fibroblasts in diseased liver. The accumulation of elastic fibers in later stages of liver fibrosis may contribute to the decreasing reversibility of the disease with advancing time. Elastin is formed by polymerization of tropoelastin monomers. It is an amorphous protein highly resistant to the action of proteases that forms the core of elastic fibers. Microfibrils surrounding the core are composed of fibrillins that bind a number of proteins involved in fiber formation. They include microfibril-associated glycoproteins (MAGPs), microfibrillar-associated proteins (MFAPs) and fibulins. Lysyl oxidase (LOX) and lysyl oxidase-like proteins (LOXLs) are responsible for tropoelastin cross-linking and polymerization. TGF-β complexes attached to microfibrils release this cytokine and influence the behavior of the cells in the neighborhood. The role of TGF-β as the main profibrotic cytokine in the liver is well-known and the release of the cytokines of TGF-β superfamily from their storage in elastic fibers may affect the course of fibrosis. Elastic fibers are often studied in the tissues where they provide elasticity and resilience but their role is no longer viewed as purely mechanical. Tropoelastin, elastin polymer and elastin peptides resulting from partial elastin degradation influence fibroblastic and inflammatory cells as well as angiogenesis. A similar role may be performed by elastin in the liver. This article reviews the results of the research of liver elastic fibers on the background of the present knowledge of elastin biochemistry and physiology. The regulation of liver elastin synthesis and degradation may be important for the outcome of liver fibrosis.